Analysis of the Asociation Between Service Quality, Hospital Image and Inpatient Loyalty - Netie Rahmayani; Ratno Adrianto; Annisa Nurrachmawati (Indonesian Journal of Global Health Research, 2026)
Competition among hospitals required improvements in service quality and the strengthening of hospital image to retain patients. Good service quality and a positive hospital image influenced patients’ trust and their decision to return for treatment. Patient loyalty became an important indicator of service success, making it necessary to analyze the factors that affected.  it. This study aims to analyze the association of service quality, hospital image with the loyalty of inpatients at I.A Moeis Samarinda Public Hospital. The study population was all inpatients in the treatment room with an average number of visits per month of 835 patients. With stratified sampling technique, a sample of 156 respondents was obtained. Questionnaire instruments were used to collect data on respondent. he results of the validity test showed that all Corrected Item Total Correlation values exceeded 0.1562, while the reliability test yielded a Cronbach’s alpha coefficient of 0.980, indicating that the questionnaire was valid and reliable. Data analysis using regression logistic biner. The results of the three independent variables test simultaneously show that the technical quality variable is positively and significantly associated with loyalty (p value = 0.016), and hospital image is positively and significantly associated with loyalty (p value = 0.000). The most dominant variable associated is hospital image with OR = 9.589 (95% CI OR = 3.064-30.006), which means that a good hospital image has a 9.5 times chance of creating patient loyalty. The conclusion of this study is the technical quality and the hospital image are positively and significantly associated with loyalty and the hospital image is the most dominant variable associated with the loyalty of inpatients.